2004
DOI: 10.1111/j.1398-9219.2004.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nucleation of Golgi Apparatus Assembly from the Endoplasmic Reticulum in Interphase HeLa Cells

Abstract: Models of Golgi apparatus biogenesis and maintenance are focused on two possibilities: one is self‐assembly from the endoplasmic reticulum, and the other is nucleation by a stable template. Here, we asked in three different experimental situations whether assembly of the Golgi apparatus might be dynamically nucleated. During microtubule depolymerization, the integral membrane protein p27 and the peripheral Golgi protein GM130, appeared in newly formed, scattered Golgi elements before three different Golgi appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 49 publications
5
31
1
Order By: Relevance
“…In sum, Golgi assembly is slow at 32°C with both cis-and trans-golgins accumulating more rapidly into post-ER punctate structures than a Golgi glycosyltransferase. The slow accumulation of GalNAcT2 into post-ER structures is consistent with data trends reported earlier at higher temperatures (Puri and Linstedt, 2003;Kasap et al, 2004). Note: the 2-h accumulation of GalNAcT2 into perinuclear patches was consistent with that observed for tsO45G, albeit GPP130 was slow.…”
Section: The Accumulation Of Medial Glycosyltransferases/ Glycosidasesupporting
confidence: 80%
See 3 more Smart Citations
“…In sum, Golgi assembly is slow at 32°C with both cis-and trans-golgins accumulating more rapidly into post-ER punctate structures than a Golgi glycosyltransferase. The slow accumulation of GalNAcT2 into post-ER structures is consistent with data trends reported earlier at higher temperatures (Puri and Linstedt, 2003;Kasap et al, 2004). Note: the 2-h accumulation of GalNAcT2 into perinuclear patches was consistent with that observed for tsO45G, albeit GPP130 was slow.…”
Section: The Accumulation Of Medial Glycosyltransferases/ Glycosidasesupporting
confidence: 80%
“…Similarly, Puri and Linstedt (2003) find that GM130 accumulates early in post-ER structures. In previous work, we have shown that a member of the p24 family of transmembrane proteins is an early component of such structures (Kasap et al, 2004). We found in our experiments no evidence for a bolus of Golgi proteins and lipids emerging as a group from the ER.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Studies have, therefore, been restricted to analysis of Golgi reassembly after treatment with drugs such as Brefeldin A (11)(12)(13)(14), although it is not clear to what extent this is a suitable model for biogenesis.…”
mentioning
confidence: 99%